The Role of Good Corporate Governance in Moderating Credit Risk and Performance of Rural Banks - Dewi, Putu Pande R. Aprilyani; Budiadnyani, Ni Putu; Prena, Gine Das (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2025)
Purpose: This study aims to determine how credit risk affects the financial performance of rural banks (BPRs) and how good corporate governance can weaken this influence. The main objective is to improve the performance of BPRs through effective risk management and transparent governance. Methodology: This research uses quantitative research methods with a sample of 205 data from 18 BPRs in North Sulawesi. The sample determination was done using purposive sampling method. Data were analysed to understand the relationship between credit risk and firm performance, as well as the role of corporate governance in weakening the effect of credit risk. Finding: The results show that credit risk has a significant influence on firm performance, but good corporate governance can weaken this influence. This suggests that effective governance implementation can help BPRs better manage credit risk and improve financial performance. Implication: This research has practical implications for BPRs in developing stronger risk management systems and more transparent decision-making processes. Thus, BPRs can improve financial performance and attract investors through effective and transparent governance. Originality: This research makes an original contribution by focusing on the role of corporate governance in weakening the effect of credit risk on BPR performance. It also provides insights into how BPRs can improve financial performance through effective risk management and good governance in specific regions such as North Sulawesi.